Monitoring the agri-food system in Myanmar: Mechanization service providers – July 2023 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
A phone survey was conducted in July 2023 to understand the effects of political instability on Myanmar’s mechanization service providers (MSPs) that are crucial for enabling smallholder farmers to undertake a range of power-intensive farm and post-harvest operations in a timely manner. This note reports on the results of this survey, which is the 11th in a series of phone surveys, as well as on trends from earlier surveys.